DETERMINANTS OF PORTFOLIO INVESTMENT IN ASEAN COUNTRIES - Firmansyah, Muhammad; Yuli, Sri Budi Cantika; Boedirochminarni, Arfida; Flejterski, Stanislaw; Kurniawan, Mahrus Lutfi Adi (Fakultas Ekonomi dan Bisnis Universitas Tanjungpura, 2025)
Portfolio investment is a key indicator of financial market health and an important driver of economic growth in ASEAN through increased liquidity and competitiveness. This study analyzes the effect of credit growth, political stability, governance, and labor on portfolio investment in ASEAN countries. A quantitative design was applied using secondary panel data from seven ASEAN countries from 2017 to 2023. Data were analyzed using the System Generalized Method of Moments (SYS-GMM) to address endogeneity and dynamic panel bias. Results reveal that credit growth significantly enhances financial market liquidity and company performance, while political stability strengthens investor confidence by providing a secure environment. Good governance reduces risk and fosters economic stability, while skilled labor supports investment attractiveness. This study concludes that political stability, healthy credit management, and strong governance are essential for attracting portfolio investment flows in ASEAN. Governments in the ASEAN region must improve governance transparency, provide training programs to improve labor skills, and maintain political stability to create a conducive investment climate.JEL: E22, E51, F66.